A benzothiazole-conjugated hemicyanine dye as a ratiometric NIR fluorescent probe for the detection and imaging of peroxynitrite in living cells. Issue 42 (16th October 2019) - Guria, Uday Narayan; Gangopadhyay, Ankita; Ali, Syed Samim; Maiti, Kalipada; Samanta, Sandip Kumar; Manna, Srimanta; Ghosh, Asim Kumar; Uddin, Md. Raihan; Mandal, Sukhendu; Mahapatra, Ajit Kumar
Abstract : We report here a new red emitting ratiometric fluorescent probe containing a benzothiazole–hemicyanine scaffold (BPVI ) linked with a CC double bond, which is a highly selective and sensitive sensor for peroxynitrite (ONOO − ) in biological systems. Abstract : Herein, we report a new red-emitting ratiometric fluorescent probe containing a benzothiazole-hemicyanine scaffold (BPVI ) linked with a CC double bond, which is highly selective and sensitive for the detection of peroxynitrite (ONOO − ) in biological systems. The dual colorimetric and ratiometric fluorescent response of the probe BPVI was due to the peroxynitrite-induced oxidation of the central double bond, which inhibited the intramolecular charge-transfer (ICT) process. The probe BPVI showed a rapid response to ONOO − over other reactive ROS/RNS at room temperature, and an attractive ratiometric fluorescence change from contessa (red region) to sapphire blue was observed in the presence of ONOO −, which was well justified in terms of ESIPT and ICT. Moreover, in the presence of competitive ROS species, our probe did not show any significant changes in both color and emission intensity ratio ( I 522 / I 702 ); this proved the high selectivity and sensitivity of the probe BPVI towards ONOO −, with a very low limit of detection (LOD, 37.0 nM). To verify the electronic properties of the BPVI probe, DFT and TDDFT calculations were performed. Moreover, it was found that the auto-fluorescence of biomolecules in living systems and aqueous solution did not significantly affect the detection procedure; the utility of the BPVI probe in the detection of ONOO − in live cells was also indicated using adenocarcinomic human alveolar basal epithelial cells.